Discrete liquid level fiber sensor - Muhammad Yusof Mohd Noor; Ahmad Sharmi Abdullah; Asrul Izam Azmi; Mohd Haniff Ibrahim; Mohd Rashidi Salim; Norazan Kassim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
A novel simple fiber sensor to sense liquid level is presented. The operation principle is based on the relative Fresnel reflective intensity. The sensor consists of a fiber splitter with the configuration of one input to multiple fiber outputs, i.e. 1×4, 1×8 and 1×12 arrangements that act as a discrete liquid level. A broadband source (BBS) is used as the light source supply. The total reflected power intensity is measured using a power meter. Experimental results show that the power intensity decreases as the level of liquid is increased. The sensor has a simple configuration, low cost, and it can be customized for a wide height measurement range spanning from a few centimeters up to a hundred meters.